Research Advances in Genetic Mechanisms of Major Cucumber Diseases Resistance - He, Yujin; Wei, Mingming; Yan, Yanyan; Yu, Chao; Cheng, Siqi; Sun, Yihan; Zhu, Xiangtao; Wei, Lingling; Wang, Huasen; Miao, Li (Frontiers in Plant Science, 2022)
Cucumber (Cucumis sativus L.) is an important economic vegetable crop worldwide that is susceptible to various common pathogens, including powdery mildew (PM), downy mildew (DM) and Fusarium wilt (FM). In cucumber breeding programs, identifying of disease resistance and related molecular markers is generally a top priority. PM, DM and FW are the major diseases of cucumber in China that cause severe yield losses, and the genetic-based cucumber resistance against these diseases has been developed over the last decade. Still, the molecular mechanisms of cucumber disease resistance remain unclear. In this review, we summarize recent findings on the inheritance, molecular markers and quantitative trait locus mapping of cucumber PM, DM and FM resistance. In addition, several candidate PM, DM and FM resistance genes with or without functional verification are reviewed. The data help reveal the molecular mechanisms of cucumber disease resistance and provide exciting new opportunities for further resistance breeding.